pH-Responsive Cross-Linked Low Molecular Weight Polyethylenimine as an Efficient Gene Vector for Delivery of Plasmid DNA Encoding Anti-VEGF-shRNA for Tumor Treatment - Li, Xiaoming; Guo, Xiaoshuang; Cheng, Yuan; Zhao, Xiaotian; Fang, Zhiwei; Luo, Yanli; Xia, Shujun; Feng, Yun; Chen, Jianjun; Yuan, Wei-En (Frontiers in Oncology, 2018)
RNA interference (RNAi) is a biological process through which gene expression can be inhibited by RNA molecules with high selectivity and specificity, providing a promising tool for tumor treatment. Two types of molecules are often applied to inactivate target gene expression: synthetic double stranded small interfering RNA (siRNA) and plasmid DNA encoding short hairpin RNA (shRNA). Vectors with high transfection efficiency and low toxicity are essential for the delivery of siRNA and shRNA. In this study, TDAPEI is a low molecular weight polyethylenimine derivative cross-linked with imine bonds by the conjugation of branched PEI 1800Da and 2,5-thiophenedicarboxaldehyde (TDA). It is a biodegradable cationic polymer utilized as the vector for the delivery of plasmid DNA expressing anti-VEGF-shRNA. Compared to PEI 25kDa, TDAPEI had a better performance both in cell and animal studies since our experimental results suggest its high transfection efficiency as well as significantly low toxicity.The vector did not show stimulation to innate immune response. All the results suggested that TDAPEI delivering anti-VEGF-shRNA may provide a promising method for tumor treatment.